Antifouling performance of copper-containing fused filament fabrication (FFF) 3-D printing polymer filaments for marine applications. Issue 2 (21st February 2021) - Piola, R.; Leary, M.; Santander, R.; Shimeta, J.
Abstract: 3-D printing allows for rapid prototyping and manufacture of components in a cost effective and timely manner, becoming a popular technology for oceanographic and maritime engineering applications. However, 3-D printed components are at risk of accumulating marine biofouling. This study examined the antifouling (AF) performance of three Cu-containing 3-D printing polymer filaments for potential marine use. The amount of Cu present in each filament was the primary determinant of AF performance. The lowest Cu-content (30%) filament recording 29% biofouling cover after 1 month and near 100% cover after 3 months. These AF results were comparable to polylactide acid (PLA) and acrylonitrile butadiene styrene (ABS) polymer filament controls. The medium (50%) Cu-content filament remained largely free of biofouling until 3 months (where 48% coverage was observed), after which fouling cover increased to 100% by ∼12 months. The highest Cu-content (80%) filament remained free of all macrofouling for the entire 24 months of the experiment.